Sepsis and Pleural Empyema Caused by Streptococcus pyogenes after Influenza A Virus Infection - Fumihiro Ochi; Hisamichi Tauchi; Toshihiro Jogamoto; Hiromitsu Miura; Tomozo Moritani; Kozo Nagai; Eiichi Ishii (Case Reports in Pediatrics)
Streptococcus pyogenes (also referred to as group A streptococci, GAS) causes severe invasive diseases such as bacteremia, necrotizing fasciitis, pneumonia, osteomyelitis, septic arthritis, and toxic shock syndrome in children. However, there are only a few reports on pleural empyema caused by GAS in children. Here, we report the case of a 4-year-old boy who presented with pleural empyema due to GAS after influenza A virus infection. With intravenous antibiotic administration and continuous chest-tube drainage, followed by video-assisted thoracoscopic surgery, his condition improved. During the clinical course, cytokines induced in response to the influenza virus, especially IL-1β and IL-10, were elevated 1 week after influenza A infection, but these decreased as the symptoms improved. Reportedly, the IL-10 production increases during influenza virus-bacteria superinfection. These observations suggest that the immunological mechanisms induced by the influenza virus can play an important role in influencing the susceptibility to secondary bacterial infections, such as GAS, in children.